Sonic Hedgehog (SHH) Promotes the Differentiation of Mouse Cochlear Neural Progenitors via the Math1–Brn3.1 Signaling pathway in vitro - Hu, Xiaohua (2010)
Sonic hedgehog (SHH) is essential for the development of the cochlear duct that harbors the organ of Corti. However, little is known about the molecular signaling pathway through which SHH promotes the development of the organ of Corti, especially cochlear sensory epithelial cells. In this study, we demonstrated that SHH contributes to the differentiation of cochlear neural progenitors (CNPs), which are derived from the postnatal day 1 organ of Corti in mice. Addition of SHH to CNPs increased the formation of epithelial cell islands, simultaneously activated the expression of Math1 that is a transcription factor for the initial differentiation of auditory hair cells. The increased expression of Math1 then regulated the promoter activity of Brn3.1, another transcription factor that controls the further differentiation and survival of auditory hair cells. Taken together, our data suggest that SHH plays an important role in the promotion of auditory hair cell differentiation via the Math1-Brn3.1 signaling pathway.